The Effect of Motivation and Career Development on Organizational Commitment at Employees PT. XXX - Muhammad Jasrol; Darma Saputra; Suyono Suyono (LAFADZ JAYA Publisher, 2022)
The purpose of this study was to examine the effect of motivation and career development on organizational commitment among PT. XXX. The research population is 879 employees. This research is associative research, namely research that aims to determine the relationship between two or more variables. With the research instrument, namely the validity test which shows that the data obtained is valid and reliable and the research results show that there is no classical assumption. Research shows that motivation has a value of 4.709 and Adjusted R Square of 0.172. In addition, after conducting the research, the value of tcount > ttable is 2.584 > 1.666. This indicates that motivation has a positive effect on organizational commitment. Career development has a score of 4, 013 and Adjusted R Square of 0.172. In addition, after conducting the research, tcount > ttable is 4.029 > 1.666. This indicates that career development has a positive effect on organizational commitment. Variables of motivation and career development have a positive effect on organizational commitment, this is evidenced by the results of the research Fcount > Ftable, namely 10.234 > 3.10.